Needle core biopsy for breast lesions: An audit of 467 needle core biopsies - Selvi Radhakrishna; Anu Gayathri; Deepa Chegu (Indian Journal of Medical and Paediatric Oncology)
Background: Breast cancer is the commonest cancer among women in urban India. Triple assessment includes clinical, radiological and cytological assessment of breast lesions. Guided core needle biopsy has replaced fine needle aspiration cytology in most of the western countries. In resource poor countries FNAC is still a very valuable and cost effective method to diagnose breast lesions. Pitfalls include increased rates of non diagnostic smears, and inadequate smears. Further procedures may be required and this increases the cost, anxiety and delay in diagnosis. Aims: The aim of this study is to analyze the concordance of radiological and histopathology findings in BI-RADS category 3,4,5 lesions following a core biopsy. Materials and Methods: Data was retrospectively collected from consecutive symptomatic and opportunistic screen detected patients with abnormalities who underwent ultrasound guided interventional procedures from Jan 2010 to Aug 2011. Symptomatic patients underwent clinical examination, mammogram and breast ultrasound. Women under 35 years of age had only breast ultrasound. Core biopsy was performed under ultrasound guidance or clinically by a breast surgeon/ radiologist for BI-RADS category 3,4,5 lesions. Statistical Methods: Chi square test was done to show the strength of association of imaging findings and histopathology results of core biopsy. Results: 437 patients were symptomatic and 30 patients had screen detected abnormalities. The positive predictive value for BI-RADS 5 lesions for malignancy is 93.25% and the negative predictive value of BI-RADS category 3 lesions for cancer is 98.4%. False negative diagnosis on core biopsy was 0.85%. We were able to defer surgery in 60% of the patients with a clear radiological and pathological benign diagnosis. Conclusion: The PPV and NPV for cancer is high with needle core biopsy in BI-RADS 3,4,5 lesions. Where there is no discordance between clinical, radiology and pathology findings, surgery can be avoided in benign lesions. While in resource poor countries FNAC continues to be a valuable method in the diagnosis of palpable and non palpable breast lesions, the practice of needle core biopsy provides the most accurate and optimal diagnostic information.